Health waste management: an educational program from knowledge to practice - Abarca Fernández, Denices (2018)
The research was conducted in order to determine the impact of education program on the knowledge and practices of solid waste management of the cleaning staff of reference Hospitals of the Puno-Peru. The study was pre experimental with pre and post test design. The sample was 44 workers determined by inclusion and exclusion criteria. The instrument used to evaluate their knowledge base was a questionnaire. As to the practices, a compliance checklist about handling solid waste by the Ministry of Health was used. The post test was applied 30 days after the application of the educational program. Data analysis was performed on a percentage basis and the testing of the hypothesis test with the Wilcoxon. The results of the training program were the following: the level of knowledge increased in conditioning from deficient (97.73%) to good (63.64%); segregation / primary storage and intermediate storage of deficient (93.18%) to good 81.82% and 77.27% respectively; Internal transport, from deficient (95.45%) to good (70.45%); final storage, from deficient (100%) to good (50%); treatment, from deficient (68.18%) to good (95.45%); collection and external transportation from deficient (75%) to good (65.91%); final disposition, from deficient (97.73%) to good (77.27%.  Regarding the practices, it improved in the conditioning stages from very poor (83.72%) to acceptable (69.76%); intermediate storage from very poor (95.35%) to acceptable (60.47%); Internal transportation / collection from very poor (100%) to acceptable (60.47%). Therefore, the education program with Andragogic model is effective to improve knowledge and practices, confirmed, with a significance level of p = 0.000